E-Government Implementation on the Example of Georgia - Tskhadadze Ketevan (TalTech Journal of European Studies)
The term ‘digitalization’ of public administration, used as a synonym for ‘e-government,’ fi rst implies the implementation of fast, secure procedures by an administrative body. E-governance, or as it is more recently termed, digital governance, involves the introduction of innovations and technologies in public governance/administration. It can be argued that the digitalization of public administration against the background of contemporary social challenges may be the key of opportunities for both the state and members of the society. Despite its certain conditionality, the electronic governance index (since 2003, the United Nations has issued a comparative index of countries’ e-governance every two years, based on three main indicators) profi ciently reflects the dynamics of countries’ efforts in introducing innovations in public administration and involving citizens in the process of e-services, which ultimately contributes to bringing citizens closer to modern digital administration.